Intrapericardial cardiosphere-derived cells hinder epicardial dense scar expansion and promote electrical homogeneity in a porcine post-infarction model - Carta-Bergaz, Alejandro; Ríos-Muñoz, Gonzalo R.; Crisóstomo, Verónica; Sánchez-Margallo, Francisco M.; Ledesma-Carbayo, María J.; Bermejo-Thomas, Javier; Fernández-Avilés, Francisco; Arenal-Maíz, Ángel (Frontiers in Physiology, 2022)
The arrhythmic substrate of ventricular tachycardias in many structural heart diseases is located in the epicardium, often resulting in poor outcomes with currently available therapies. Cardiosphere-derived cells (CDCs) have been shown to modify myocardial scarring. A total of 19 Large White pigs were infarcted by occlusion of the mid-left anterior descending coronary artery. Baseline cardiac magnetic resonance (CMR) imaging with late gadolinium enhancement sequences was obtained 4 weeks post-infarction and pigs were randomized to a treatment group (intrapericardial administration of 300,000 allogeneic CDCs/kg), (n=10) and to a control group (n=9). A second CMR and high-density endocardial electroanatomical mapping were performed at 16 weeks post-infarction. After the electrophysiological study, pigs were sacrificed and epicardial optical mapping and histological studies of the heterogeneous tissue of the endocardial and epicardial scars were performed. In comparison with placebo, intrapericardial CDCs reduced the growth of epicardial dense scar and epicardial electrical heterogeneity. The relative differences in conduction velocity and action potential duration between healthy myocardium and heterogeneous tissue were significantly smaller in the CDC-treated group than in the placebo group. The lower electrical heterogeneity coincides with heterogeneous tissue with less fibrosis, better cardiomyocyte viability, and a greater quantity and better polarity of connexin 43. At the endocardial level, no differences were detected between groups. Intrapericardial CDCs produce anatomical and functional changes in the epicardial arrhythmic substrate, which could have an anti-arrhythmic effect.